2011
DOI: 10.1017/s0031182011001880
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiinfection in pregnant women in China

Abstract: Toxoplasmosis, caused by the protozoan parasite Toxoplasma gondii, is one of the most common parasitic infections in humans. Primary infection in pregnant women can be transmitted to the fetus leading to miscarriage or congenital toxoplasmosis. Carefully designed nationwide seroprevalence surveys and case-control studies of risk factors conducted primarily in Europe and America, have shaped our view of the global status of maternal and congenital infection, directing approaches to disease prevention. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 29 publications
9
46
1
2
Order By: Relevance
“…The 82.3 % Toxoplasma IgG positive and lgM negative results obtained in this study was similar with study from Jimma town, Ethiopia [25] and higher than those studies reported from Central Ethiopia [16] and elsewhere in the world [36–40]. In this study, 3.02 % of enrolled pregnant women had detectable IgM antibodies during pregnancy with potential risk of congenital T. gondii infection warranting attention to design preventive measures.…”
Section: Discussionsupporting
confidence: 88%
“…The 82.3 % Toxoplasma IgG positive and lgM negative results obtained in this study was similar with study from Jimma town, Ethiopia [25] and higher than those studies reported from Central Ethiopia [16] and elsewhere in the world [36–40]. In this study, 3.02 % of enrolled pregnant women had detectable IgM antibodies during pregnancy with potential risk of congenital T. gondii infection warranting attention to design preventive measures.…”
Section: Discussionsupporting
confidence: 88%
“…Acute infection with T. gondii during pregnancy and its potentially tragic outcome for the fetus and newborn continue to occur worldwide (21), with a significant proportion of pregnancies being at risk (32,33). Toxoplasmosis is being recognized with increased frequency, especially in patients with AIDS (34).…”
Section: Discussionmentioning
confidence: 99%
“…In an immunocompetent host, infection is generally chronic and asymptomatic, as the immune system keeps T. gondii confined to cysts and the intracellular space within the muscle and brain. Primary infection in pregnant women can be transmitted to the fetus leading to miscarriage or congenital toxoplasmosis [116]. T. gondii, is diagnosed mainly by serological methods that are hindered by insufficient sensitivity.…”
Section: Toxoplasma Infectionmentioning
confidence: 99%